Housing planning and development in developing country: a case of Nigerian government - Abdullahi, Hashim; Asmawi, M. Zainora (Pyla-mak Services, 2017)
This book discusses about the housing aspect in the context of Nigeria. Basically it covers the fundamental aspects, i.e. housing standards, housing finance, the importance of housing to man, housing problems, housing market, demand and supply, housing and environment and housing and population.